Lohnungleichheit – Gibt es eine Trendwende? - Joachim Möller (Wirtschaftsdienst, 2016)
– Using a large panel microdata set for the time period 1992 to 2014, the paper analyses the long-run trends in German wage inequality for full-time workers. The approach differentiates by gender and region. The analysis confirms the result of other studies that show a sharp increase in wage inequality in Germany from the mid-1990s until 2010. The increase can only partly be explained by rising skill differentials. The lion's share is neither attributable to price effects nor to changes in the composition of the workforce. As an interesting phenomenon, the rise in the inequality indicators did not continue after 2010. The pattern is similar for male and female workers as well as for the eastern and western parts of the country. In some sub-samples we even find a marked decline. This is especially true for females. Hence there are some indications of a hiatus or even a trend reversal. At the time being it is still unclear whether the phenomenon is caused by sectoral minimum wages, a more egalitarian stance on wage policy, technological or structural developments favouring the low-skilled or other causes.
Keywords: J31; D31; D63; 330; Lohnstruktur; Niedriglohn; Geschlechterunterschiede; Räumliche Verteilung; Deutschland